2018
DOI: 10.1056/nejmoa1802712
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Risk of Stroke after TIA or Minor Ischemic Stroke

Abstract: In a follow-up to a 1-year study involving patients who had a TIA or minor stroke, the rate of cardiovascular events including stroke in a selected cohort was 6.4% in the first year and 6.4% in the second through fifth years. (Funded by AstraZeneca and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
231
5
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(276 citation statements)
references
References 16 publications
17
231
5
16
Order By: Relevance
“…15 Recent studies adjusting for competing risk of death have reported 1-and 5-year incidences of recurrence of 3.6%-7.7% and 10.1%-16.8%. [16][17][18][19] Our results are thus supporting newer data from several other populations.…”
Section: Discussion/con Clus Ionsupporting
confidence: 87%
“…15 Recent studies adjusting for competing risk of death have reported 1-and 5-year incidences of recurrence of 3.6%-7.7% and 10.1%-16.8%. [16][17][18][19] Our results are thus supporting newer data from several other populations.…”
Section: Discussion/con Clus Ionsupporting
confidence: 87%
“…In recent decades, several studies conducted in a wide range of different settings have focused on the association between transient ischaemic attack (TIA) and the risk of stroke [3][4][5][6][7][8][9][10][11][12][13][14]. Whilst these results have shed some light on the association between TIA and stroke, they also have had several limitations that must be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, most of the recent studies followed participants for 5 years or less [7][8][9][10]13], so the long-term risk of stroke and associated predictors in patients with a history of TIA remains largely unknown. Thirdly, only one previous study was conducted in Germany [10] and, given that stroke incidence is particularly high in Germany [16], more research investigating risk factors for this neurological condition in this country is needed.…”
Section: Introductionmentioning
confidence: 99%
“…mirabegron | atherosclerosis | plaque instability | lipolysis | adipose tissue A therosclerosis, the thickening, hardening, and loss of elasticity of the arterial vessel wall, is the major cause of morbidity and mortality worldwide (1)(2)(3)(4). Atherosclerotic lesions containing fatty plaques, cholesterol, and inflammatory cells are the primary causes of cardiovascular disease and stroke (5,6). Atherosclerosis as a chronic and progressive disease usually starts with damage of the endothelial layer of an artery.…”
mentioning
confidence: 99%